2004
DOI: 10.1080/10640260490521389
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Study of Cognitive Behavior Therapy and Behavioral Family Therapy for Anorexia Nervosa Patients

Abstract: Very few studies have examined the role of cognitive behavior therapy (CBT) in the outpatient treatment of anorexia nervosa. This study used a randomized, controlled design to evaluate a 12-month, manual based program of CBT, with behavioral family therapy as the comparison group. Twenty-five adolescents and young adults with anorexia nervosa, currently living with their families, were recruited into the study with both treatment groups receiving 21-25 sessions of therapy. Outcome measures included nutritional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
1
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(86 citation statements)
references
References 29 publications
2
77
1
6
Order By: Relevance
“…6,22,23,26,28 However, the effect sizes between the instruments used to measure the traits differed. The effect size in two studies reporting pre and post scores using the YBC-ED were 0.89 (ritual and preoccupation scale) 22 and 0.75 for long, versus 0.48 for short, family therapy.…”
Section: Rct Study Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…6,22,23,26,28 However, the effect sizes between the instruments used to measure the traits differed. The effect size in two studies reporting pre and post scores using the YBC-ED were 0.89 (ritual and preoccupation scale) 22 and 0.75 for long, versus 0.48 for short, family therapy.…”
Section: Rct Study Analysismentioning
confidence: 99%
“…6 In the remaining studies, either predictors of outcome were not assessed, assessed but not reported, 22,30,32 or no or other more significant predictors of outcome were found. 23,26,27,29,31 In two of these studies 23,31 it was unclear whether personality variables were included in outcome analyses.…”
Section: Rct Study Analysismentioning
confidence: 99%
“…In all studies, the criterion for the diagnosis of AN was DSM-III, IV or V, depending on the time of the study. The age group selected in the studies ranged from 11 to 20 years, with mean age ranging from 13.9 years (SD = 2.1) 29 to 18.45 (SD = 2.57) 25 . Female adolescents represented the majority in all studies.…”
Section: Participantsmentioning
confidence: 99%
“…60 So far studies have provided little support for specialised psychotherapies or pharmacotherapies, conducted with both underweight and weight-restored individuals. [61][62][63][64][65][66][67][68][69] However, the Maudsley family-based therapy approach is one of the few empirical, evidencebased studies showing effectiveness in young people with AN under the age of 18 years. 70,71 Cognitive behavioural therapy (CBT) Due to some diagnostic uncertainties, an enhanced, 'trans diagnostic' approach to CBT has been established (CBT-E).…”
Section: Psychological Interventionsmentioning
confidence: 99%